Dampak Bencana Alam Terhadap Keberlangsungan Usaha Rumah Tangga Pengrajin Songket Di Nagari Halaban Kecamatan Lareh Sago Halaban Kab. Lima Puluh Kota - Zulhijatur Rahmi; Aulia Rahmi; Sucipto Febrianto; Illham Supriyadi (Institut Agama Islam Yasni Bungo Jambi, Indonesia, 2026)
Songket craft is a cultural art that must be maintained and preserved. In Nagari Halaban, songket craft is a prima donna of production that supports household income. It is estimated that around 750 songket craftsmen in Nagari Halaban are generally carried out by housewives. However, after the major flood disaster in West Sumatra, the sustainability of the household businesses of songket craftsmen in Nagari Halaban was affected. The purpose of this study is to reveal how the sustainability of the household businesses of songket craftsmen in Nagari Halaban before and after the major flood disaster, then to reveal the factors supporting the sustainability of the household businesses of songket craftsmen after the major flood disaster. This research methodology was conducted in Nagari Halaban using a phenomenological approach. The data sources in this study were songket craftsmen registered with the Halaban Weaving Association. Data analysis techniques in this study are data reduction, data presentation, and decision making. The results of the study indicate that the sustainability of the household businesses of songket craftsmen in Nagari Halaban before the major flood disaster was consistent and sustainable, while after the major flood disaster it became inconsistent, resulting in a decrease in income, thus threatening the welfare of the households of songket craftsmen in Nagari Halaban. There are three factors supporting the sustainability of songket artisan household businesses after a major flood disaster, namely capital factors, production factors, and marketing factors.